The response of a Helmholtz resonator to external excitation. Part II: Flow-induced resonance - Meissner, M. (Archives of Acoustics, 2005)
In the paper a phenomenon of sound production in a resonator driven by an air jet has been investigated. Measurements of sound spectra at the closed end of the resonator cavity were performed to determine the influence of the jet velocity on the frequency and amplitude of excited acoustic oscillations. It was found that in the sound generation process two ranges of the jet velocity could be distinguished where different variations of the oscillation frequency with the growing jet velocity were observed. After the onset of oscillation the frequency increased fast with growing jet velocity and the frequency increment was directly proportional to a value of jet velocity. At higher flow velocities an increase in the frequency was still observed, but the frequency growth was much smaller. The experiment has shown also that due to an excitation of mechanical vibrations of the resonator elements a rapid change in the oscillation frequency occurred. Finally, the experimental data were compared to calculation results to examine the accuracy of the theoretical model, in which a force driving the resonator was predicted from the vortex sound theory and the resonator was modelled by an equivalent impedance circuit. Key words: sound generation, flow-induced resonance, acoustic resonators.